Prosthetic rehabilitation of face following naso-orbital mycosis - Deshpande, S N; Bhat, S; Sharma, R; Singh, S; Fernandes, J (Indian Journal of Plastic Surgery, 2006)
Sino-nasal mycosis is a known complication in patients with immunological or metabolic compromise. Mainstay of treatment includes reversal of the compromised state, systemic antifungals and repeated radical debridements assisted by serial imaging. Salvage is possible provided no cerebral extension exists on presentation. The resultant deformity following debidement causes gross morbidity and psycho-social embarrassment. Surgical reconstruction is difficult on account of co-morbid diseases. Non-surgical prosthetic rehabilitation gives fairly accurate correction in these patients. We report a case of a 48 yrs. male diabetic with sino-orbital mycosis where debridement resulted in a gross morbid defect. However effective rehabilitation was achieved using three piece maxillo-facial prosthesis.
Keywords: Naso-orbital mycosis; prosthetic rehabilitation; surgical debridement